Adding a brake shoe temperature model into freight train longitudinal braking dynamics simulations. (May 2023) - Wu, Qing; Magelli, Matteo; Zampieri, Nicolò; Bernal, Esteban
Published research about brake shoe temperature assessments and the influences of temperature dependent brake Coefficient of friction (CoF) on train braking performance do not consider detailed train dynamics. This paper addresses this research gap by combining a brake shoe temperature model with a detailed Longitudinal Train Dynamics (LTD) model. A simplified one-dimensional (1D) Finite Element brake shoe temperature model was developed. Studies were conducted to assess brake shoe temperatures during cyclic air brakes and single-occurrence air brakes. Results show brake shoe temperatures at different positions of the train can be very different due to brake characteristics variations. During case studies, temperature dependent brake CoF increases train braking distances by 10.2 and 6.6% on down grade and flat tracks respectively. Emergency brake cases have the highest increases of brake distances by 11.3% on down grade tracks.